Gambaran Kualitas Hidup pada Lansia di Posyandu Sasono Mulyo IV Masaran Sragen - Sintya Diah Putri Astuti; Sitti Rahma Soleman (Inovasi Kesehatan Global, 2024)
The quality of life of older people is a measure of how good and satisfying the life experienced by an older person is, referring to their level of satisfaction and well-being. The importance of understanding and improving the quality of life of the elderly is to ensure they can enjoy old age with maximum self- esteem, well-being and happiness so that when the elderly are gone, the elderly are at peace. The quality of life of the elderly includes several domains including physical health, psychological, social relationships and the environment. For prevalence in posyandu sasono mulyo IV has 384 elderly. Objective: To determine the description of quality of life in the elderly at Posyandu Sasono Mulyo IV Masaran Sragen. Methods: This study uses a quantitative descriptive method, the number of samples obtained from the calculation of the Slovin formula is 79 respondents. Results: The results of this study found that in general the description of the quality of life of the elderly was in the poor category as many as 71 respondents or 89.9%, while the moderate category was 8 respondents or 10.1%. Conclusion: The quality of life of the elderly in Posyandu Sasono Mulyo IV is generally in the poor category.